Perancangan Inventory System untuk Mengoptimalkan Operasional Penjualan, Pembelian, dan Pengembalian pada CV.Victory - Faustin Christiane; Devi Tanria; Julius Sutrisno (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In company operations, of course you need records in the form of stock data and transaction data to make reports. Likewise with CV. Victory has used software to optimize the company's operations, but the software still has many shortcomings so that the company's operations are not optimal. There is a proposed solution, namely the design of a desktop-based inventory application with the aim of supporting company efficiency and productivity. In this Digital Business Project, the method used is the waterfall methodology which consists of requirements analysis, system design and testing. The type of research used is qualitative research by conducting an interview process with the resource person, namely the Chief Operational Officer from CV. Victory. by asking several questions related to problems occurring in the company with the aim of being a guide to designing solutions.The result of the project is an analysis of business flow, system flow, business model, then the final result is a desktop-based application design that has various features in it according to the company's needs. The features available in the application include goods data, supplier data, customer data, employee data, and transaction data (sales, purchases and returns). These features, apart from being able to enter data, also provide access to update and delete. After the application design has been created, a feasibility analysis is carried out to determine whether the development of the system project is worth continuing or stopping, and the results obtained are that the application design created is declared feasible according to the results of behavioral testing or what can be called black box testing.The conclusion of this project is that the design of a desktop-based inventory application will definitely provide company efficiency and productivity by providing process automation, smoother work flow, and faster access to information, so that it can save time, costs, resources, and improve service quality.